Pendapatan dan kontribusi generasi Y terhadap kesadaran membayar zakat dengan pembayaran zakat digital sebagai variabel moderasi - Bila, Azahra Salsa; Nurhadi, Bayu (Nur Science Institute, 2024)
The awareness of paying zakat is a form of social and spiritual responsibility that reflects concern for the community's welfare. This research aims to determine the influence of income and the contribution of Generation Y to the awareness of paying zakat with digital zakat payment as a moderation variable. This study uses a quantitative method by processing primary data. The data was collected through a questionnaire distributed to Generation Y in Indonesia. The sample used in this study was 300 respondents. Data analysis methods include instrument tests, classical assumption tests, statistical tests, and MRA tests. The results of this study show that based on the T-test, it is stated that the income and contribution variables of Generation Y have a significant positive effect on the awareness of paying zakat. Based on the results of the F test, it is stated that Generation Y's income and contribution variables significantly influence their awareness of paying zakat. The MRA test shows that the digital zakat payment variable can moderate the influence of income and the contribution of Generation Y on the awareness of paying zakat.